Significant photoresponsivity enhancement of polycrystalline BaSi2 films formed on heated Si(111) substrates by sputtering. (4th June 2018) - Matsuno, Satoshi; Takabe, Ryota; Yokoyama, Seiya; Toko, Kaoru; Mesuda, Masami; Kuramochi, Hideto; Suemasu, Takashi
Abstract: We fabricated approximately 200-nm-thick BaSi2 films on Si(111) substrates at 600 °C. The formation of BaSi2 was demonstrated by X-ray diffraction and Raman spectroscopy. A reduction in the electron concentration ( n = 2 × 10 16 cm −3 ) by 3 orders of magnitude compared to that previously reported ( n = 7 × 10 19 cm −3 ) and resultant photoresponsivity enhancement by more than two orders of magnitude were achieved. The photoresponsivity increased with the bias voltage V bias applied between the top and bottom electrodes, and reached approximately 0.19 A/W at 2.0 eV, room temperature, and | V bias | = 0.5 V.